Investment Law and the Right to Regulate Public Health and Environmental Protection (Journal of Social Sciences Review, 2024)
This article explores the tension between investment law protections and a state’s right to regulate public health and environmental protection. International investment agreements (IIAs) provide strong protections for foreign investors, often limiting host states’ regulatory freedoms. This dynamic can create challenges when states seek to implement policies for public welfare that may impact foreign investments. The study examines case law, such as Philip Morris v. Uruguay and Vattenfall v. Germany, to highlight conflicts between investor rights and regulatory measures. Through a review of recent treaties, including the Comprehensive Economic and Trade Agreement (CETA) and the United States-Mexico-Canada Agreement (USMCA), the article identifies emerging mechanisms like explicit right-to-regulate clauses, carve-outs, and interpretive guidelines designed to balance investment protection with the public interest. The results indicate that some protections are provided by new treaty provisions, but interpretive flexibility and a lack of automaticity in procedural aspects of arbitration can create as-yet unresolved challenges. It recommends that investment law reforms go further and focus on placing the public interest at the heart of investment law, establishing an architecture supportive of sustainable development, and enabling states to respond to pressing health and environmental problems without running the risk of investor claims.
Keywords: Arbitration; Bilateral Investment Treaties; Environmental Governance; Expropriation; Public Policy; Regulatory Autonomy; Sustainable Development